SOD2 polymorphisms: unmasking the effect of polymorphism on splicing - Shao Jing; Chen Lishan; Marrs Brian; Lee Lin; Huang Hai; Manton Kenneth G; Martin George M; Oshima Junko (BMC, 2007)
Abstract Background The SOD2 gene encodes an antioxidant enzyme, mitochondrial superoxide dismutase. SOD2 polymorphisms are of interest because of their potential roles in the modulation of free radical-mediated macromolecular damage during aging. Results We identified a new splice variant of SOD2 in human lymphoblastoid cell lines (LCLs). The alternatively spliced product was originally detected by exon trapping of a minigene in order to examine the consequences of an intronic polymorphism found upstream of exon 4 (nucleotide 8136, 10T vs 9T). Examination of the transcripts derived from the endogenous loci in five LCLs with or without the intron 3 polymorphism revealed low levels of an in-frame deletion of exon 4 that were different from those detected by the exon trap assay. This suggested that exon trapping of the minigene unmasked the effect of the 10T vs 9T polymorphism on the splicing of the adjacent exon. We also determined the frequencies of single nucleotide polymorphisms in a sample of US African-Americans and non-African-Americans ages 65 years and older who participated in the 1999 wave of the National Long Term Care Survey (NLTCS). Particularly striking differences between African-Americans and non-African-Americans were found for the frequencies of genotypes at the 10T/9T intron 3 polymorphism. Conclusion Exon trapping can unmask in vitro splicing differences caused by a 10T/9T intron 3 polymorphism. Given the recent evidence that SOD2 is in a region on chromosome 6 linked to susceptibility to hypertension, it will be of interest to investigate possible associations of this polymorphism with cardiovascular disorders.